Олень у палеолітичному наскельному мистецтві франко-кантабрійського регіону - Михайлова, Н. (Студії мистецтвознавчі, 2008)
There cult of the deer was widespread in traditional societies of deer hunters. The most important evidence supporting a deer cult in traditional societies are the totemistic and cosmological myths and rituals, connected with the reproduction and regeneration of the deer, the ancestor of people and deer.